Contemporary Qurban Transactions: Are There any Ghoror Practices? - Najmi; Maulana Hamzah, Muhammad (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2024)
This study aims to examine research related to ghoror practices in qurban transactions in Indonesia and provide input solutions to eliminate ghoror and open discourse for further research. This study used a qualitative approach with the literature review method. The researcher examines research related to the practice of qurban transactions in Indonesia in journals and proceedings that are indexed by Sinta or have an ISSN. As well as normative descriptive methods to examine the ghoror aspects of transactions and solutions to eliminate them. Research divides qurban transactions into 3, namely qurban transactions using Islamic financial institutions, online qurban transactions and offline qurban transactions through mosques or Islamic schools. The result is that there are 4 types of ghoror that occur, namely ghoror in the contract, ownership, specifications for animals and guarantees. This research also provides solutions to every ghoror issue that occurs. In addition, more specific research on one type of transaction by adding samples from Scopus and WoS journals can expand the results of research that has been done. This study found that financial transaction innovations in qurban worship have the potential to cause ghoror in both financial transactions and reports. This research provides input so that qurban transactions and innovations that will be made are free from forbidden ghoror practices.